Pain in the acute phase of Guillain–Barré syndrome. Issue 2 (16th May 2014) - Kinboshi, Masato; Inoue, Manabu; Kojima, Yasuhiro; Ono, Michio; Nakagawa, Tomokazu; Kanda, Masutaro; Shibasaki, Hiroshi
Abstract Background and Aim Pain has not been recognized as a main feature of Guillain–Barré syndrome (GBS) in its acute phase. The pathophysiology of pain and its effect on the prognostic outcome of GBS have not been fully evaluated. The aim of the present study was to report the clinical features and prognosis of GBS patients presenting with pain in the acute phase. Methods This was a retrospective study of 34 consecutive patients with GBS. We compared clinical profiles and laboratory findings between the GBS patients with pain and those without pain. Results A total of 29% of GBS patients had pain in the acute phase. Among others, low back pain was most common. GBS patients with pain were significantly younger than those without pain. In GBS patients with pain, the time of admission, the time for starting treatment and the time of discharge from the hospital were significantly delayed as compared with those without pain. However, there was no difference in the preceding infections, laboratory findings, or disability at the time of nadir and discharge. Conclusion Pain is relatively common in the acute phase of GBS. Young GBS patients are especially susceptible to pain. Pain in the acute phase of GBS delays the time for reaching the correct diagnosis, and prolongs the duration of hospital stay and recovery, although it does not influence the functional prognosis.